2013
DOI: 10.4161/cc.26388
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-β5 and zyxin mediate formation of ventral stress fibers in response to transforming growth factor β

Abstract: Cell adhesion to the extracellular matrix is an essential element of various biological processes. TGF-β cytokines regulate the matrix components and cell-matrix adhesions. The present study investigates the molecular organization of TGF-β-induced matrix adhesions. The study demonstrates that in various mouse and human epithelial cells TGF-β induces cellular structures containing 2 matrix adhesions bridged by a stretch of actin fibers. These structures are similar to ventral stress fibers (VSFs). Suppression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…Paxillin phosphorylation is mediated predominantly by Src family kinases (Schaller, 2001), and our Bio-ID assay revealed that GIT2, a Src substrate, was enriched proximal to paxillin in TGFβ-treated MCF10A MECs (enrichment factor, ∼4; Yu et al. , 2009, 2010; Bianchi-Smiraglia et al. , 2013; Figure 8b).…”
Section: Resultsmentioning
confidence: 99%
“…Paxillin phosphorylation is mediated predominantly by Src family kinases (Schaller, 2001), and our Bio-ID assay revealed that GIT2, a Src substrate, was enriched proximal to paxillin in TGFβ-treated MCF10A MECs (enrichment factor, ∼4; Yu et al. , 2009, 2010; Bianchi-Smiraglia et al. , 2013; Figure 8b).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, paxillin is normally binds to ɑ 5 β 1 , ɑ 4 β 1 , ɑ 5 β 3 and ɑ 4 β 3 integrins [4649], while zyxin binds to the integrin subtypes ɑ 5 β 1 and ɑ 5 β 5 [50, 51]. Besides, the integrin motifs expressed in different cell types may vary considerably.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest an important role for tropomyosin in the regulation of TGFβ‐induced cell migration. A recent study has also found that depletion of caldesmon does not impact cell adhesion to fibronectin or the formation of ventral stress fibers during TGFβ‐induced EMT in mammary epithelial cells [Bianchi‐Smiraglia et al, ]. Further experiments are necessary to elucidate the impact of caldesmon expression on other aspects of TGFβ‐induced EMT.…”
Section: Changes In the Expression Of Cytoskeletal Associated Genes Dmentioning
confidence: 99%
“…Zyxin localizes to focal adhesion sites and to stress fibers in response to mechanical cues and has been shown to regulate actin polymerization, generation of traction force, cell movement, and signal transduction [Beckerle, 1998;Kadrmas and Beckerle, 2004]. TGFb promotes the upregulation of zyxin in normal mammary epithelial cells and zyxin expression mediates actin reorganization and the formation of ventral stress fibers [Mori et al, 2009;Bianchi-Smiraglia et al, 2013;Diepenbruck et al, 2014]. During TGFbinduced EMT, zyxin expression is regulated by the transcription factor Twist1 [Mori et al, 2009] and by the canonical Smad pathway [Bianchi-Smiraglia et al, 2013].…”
Section: Zyxinmentioning
confidence: 99%
See 1 more Smart Citation